Discussion on Matrix Interference in Trace-Level Bromate Detection of Natural Mineral Water in Southwest China Karst Area - Xi YANG; Xiaolin ZHOU; Song ZHENG (Yankuang ceshi)
As a limitation of natural mineral water, bromate has potential carcinogenic risk. The World Health Organization and China National Standard have set a strict concentration limit of 0.01mg/L. The bromate in natural mineral water in the Guizhou karst area of southwest China is usually at trace levels while the chemical background of water is complex, which causes great difficulties using ion chromatography to detect the bromate due to matrix interference. Sulfate was determined as the factor of matrix interference by screening interference factors. High concentration sulfate readily occupied the stationary phase points of the chromatographic column, thus the peak of bromate was drifted and the signal response was reduced. In order to detect the trace-level bromate accurately, three detection methods were proposed: ion chromatography-conductivity detector method Ⅰ(IC-CDⅠ) used a standard addition method to eliminate matrix interference; ion chromatography-conductivity detector method Ⅱ (IC-CDⅡ) innovatively adopted Ba column to remove sulfate matrix interference; ion chromatography-inductively coupled plasma-mass spectrometry (IC-ICP-MS) employed the anti-interference mass spectrometer as a detector. The results showed that the three methods could be used to effectively eliminate the matrix interference of high concentration sulfate. The correlation coefficient of method IC-CDⅠ was 0.9993. The RSD of method IC-CDⅡ was 0.42%−0.76% and the recovery rate was 94.5%−102.7%. The RSD of method IC-ICP-MS was 0.31%−0.48% and the recovery rate was 95.9%−97.7%. Moreover, the quantitative limits of method IC-CDⅡ and method IC-ICP-MS were lower than the China National Standard. When the concentration of bromate in water was lower than 10.0μg/L, method IC-CDⅡ and method IC-ICP-MS were preferred. When the concentration was higher than 10.0μg/L, the three methods could be optionally used. The three methods provide ideas and basis for the determination of trace-level bromate in natural mineral water with high concentration sulfate matrix interference.